Affective economies of racism on social media - Rodwell Makombe; Bright Sinyonce; Mpitseng Tladi; Saneliso Thambo (Communicare)
New media technologies and social networks have not only opened up spaces for civic engagement and democratic participation, but have also offered alternative sites for the proliferation and circulation of racist, homophobic and xenophobic sentiment. This article draws on Ahmed’s idea of “affective economies” and Ekman’s (2019) notion of “affective publics” to investigate how white supremacist groups in South Africa have used social media to express racist views, attitudes and sentiments. The internet in general and social networks in particular are based on a libertarian logic that emphasises freedom of speech at the expense of the rights of minorities whose views may not meet the required algorithmic thresholds of specific social media sites. While governments around the world have put in place laws to deal with overt racism and hate speech, online platforms remain new battlegrounds for the articulation of racist views and sentiments. The findings of the study show that white supremacist groups in South Africa use social media as a platform to recontextualise and re-mediate topical issues in South African society and ramp up group solidarity by circulating racist views that undermine and de-legitimise the ruling party (the African National Congress) and its policies.